Subjetividade e educação libertadora no contexto neoliberal : a atualidade de Paulo Freire - Fortuna, Volnei (2021)
This thesis deals with the theme of subjectivity and liberating education in the neoliberal context, taking Paulo Freire's thought as a reference. The guiding question of the investigation concerns how human subjectivity is constituted in view of the predominance of the neoliberal vision in current education and what demands are presented for the formation of liberating subjectivities. Based on Freire, the guiding hypothesis considers, as its main proposition, the transformation of oppressed subjectivity into an autonomous and free subjectivity as a requirement for the formation of a fairer, more solidary and humanized society. It is about identifying and analyzing the complexity of the neoliberal reason that provokes the transformation of subjectivity into production and reproduction of the capital, restricting the meaning and the purpose of human existence and the reach of Freire's thought for the formation of liberating subjectivities. The thesis is composed of three chapters: the first one analyzes the relationship between neoliberalism, subjectivity and education; the second one reflects on Freire's educational principles, involving awareness, freedom and autonomous subjectivity; the third one seeks to extract the actuality of Freire's liberating pedagogy as an emancipatory hermeneutic exercise of individuals and groups in the current context. The research procedure is of a dialogical-dialectic-hermeneutic nature, proposing an investigation in education that enhances the transforming criticism of the formation and promotes the dialogic understanding among those involved in the educational process. It is considered, as important principles of this investigation, the commitment to the struggle for the autonomy and freedom of the oppressed, be they students or educators from different contexts of oppression. It is concluded that the updated Freirean pedagogy thinks subjectivity beyond the neoliberal model characterized by presenting a subject without a world and without intersubjective capacity. Freire's theory is a counterpoint to neoliberalismo because it leads subjects to problematize reality, making them propositional in face of the denial of human dignity. In obscure times like the present, liberating subjectivity makes possible to overcome short sightedness and intellectual presumptions, provoking subjects to ethical re-appropriation. This, in Freire, has as essential principles the lovingness, the autonomy, the humility, the solidarity and the hope of thinking about society in a democratic, dialectical and participatory way.